Benefiting from the Internet by Egyptian academics | الإفادة من الإنترنت من جانب الأكاديميين المصريين - Abdulaziz | عبد العزيز, Tahani Omar | تهاني عمر (King Fahad National Library | مكتبة الملك فهد الوطنية, 2024)
This study aims to identify the reality of Internet use among Egyptian researchers in the field of social and human sciences, in terms of the availability of components for dealing with the Internet, motives for dealing, sources of information, aspects of benefit, rates of interaction, time spent, search engines used, and the extent to which the sites meet Free services for the needs of beneficiaries, providing libraries with the capabilities to deal with non-free websites, subscribing to beneficiaries in non-free websites, and obtaining the research results in print. The study reached a number of results, the most important of which are: The most common places that provide the capabilities to use the Internet in homes are the most common, then libraries, then offices. The basic motives for dealing with the Internet are to become aware of what is new in the field of specialization, obtain documents for research purposes, and obtain materials for teaching purposes. (The rest of the text) Keywords: Internet, Egyptian researchers, social sciences and humanities. | تهدف هذه الدراسة إلى التعرف على واقع استخدام الإنترنت لدى الباحثين المصريين في مجال العلوم الاجتماعية والإنسانية, وذلك من حيث أماكن توافر مقومات التعامل مع الإنترنت, ودوافع التعامل, ومصادر المعلومات, وأوجه الإفادة, ومعدلات التعامل, والوقت المستنفد, ومحركات البحث المستخدمة, ومدى تلبية المواقع المجانية لاحتياجات المستفيدين, وتوفير المكتبات لمقومات التعامل مع المواقع غير المجانية, واشتراك المستفيدين في المواقع غير المجانية, والحصول على ناتج البحث مطبوعًا. وتوصلت الدراسة إلى عدد من النتائج أهمها: أن أماكن توافر مقومات التعامل مع الإنترنت بالمنازل هي الأكثر شيوعًا, ثم المكتبات, ثم المكاتب. أن الدوافع الأساسية للتعامل مع الإنترنت هي الإحاطة بما هو جديد في مجال التخصص, والحصول على وثائق لأغراض البحث, والحصول على مواد لأغراض التدريس.(بقية النص) الكلمات الرئيسية: الإنترنت, الباحثون المصريون, العلوم الاجتماعية والإنسانية."